Зміни клімату як загроза для флори водних макрофітів Північного Поділля - Михалюк, Ілона; Чопик, Володимир; Mykhalyuk, Ilona; Chopyk, Vladimir (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті досліджено взаємозв’язок між змінами клімату та видовим різноманіттям флори макрофітів Північного Поділля. Проаналізовано дію кліматичних чинників на зміну кількості водойм (на прикладі Кременецького району). Запропоновано прогноз змін флори макрофітів Північного Поділля. Порівняно гідрофільні флори України й Польщі за допомогою визначення коефіцієнтів подібності.Іn the article іs research the relationship between climate change and species diversity of flora of macrophytes of Northern Podillya. Established that the steady increase of air temperature, accompanied by a decrease of rainfall, causes reduction of water level in reservoirs and sometimes causes their drying. Hure is analyzed the effect of climatic factors on the change of the number of reservoirs in Northern Podillya and concluded that 60 reservoirs will dry after 200 years inthe investigated area if tare into accaunt such meteorological conditions. The comparison of hydrophilic flora of Ukraine and Poland with the helpof determining similarity coefficients of Zhakkara and Sorensen was made. The results of calculations found that hydrophilic flora that are geographically close to each other, marked by high levels of similarity.
Changing of Climate as Threat for Flora Aquatic Macrophytes of Northern Podillya
Keywords: зміни клімату; динаміка; порівняння; гідрофільна флора; Північне Поділля; Кременецький район; climate changes; dynamics; comparison; hydrophilic flora; Northern Podillya; Kremenets district